Effect of pregnancy on working women in Wilayah Persekutuan Kuala Lumpur, 1998 - Aini Rasimah A. Wahab; K.G.Rampal (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A stratified cross-sectional study to determine the prevalence of fatigue, numbness and tingling of the hands, backache, leg edema and varicose veins among three groups of women (i.e. pregnant worker, non pregnant worker and housewife) was carried out in June until August 1999 in Wilayah Persekutuan Kuala Lumpur. The pregnant women were those f registered with the D.B.K.L. antenatal clinic while the non pregnant group were D.B.K.L office workers in Jalan Raja Laut. About 89.8% (404 respondent) out of the planned 450 respondents, participated in the study. The result showed that among the non pregnant women the prevalence of fatigue was 54.90/0, that of numbness and tingling of the hands 12.9%, backache 22.0%, edema 4.0% and varicose veins 8.7%. Among the pregnant women the prevalence of fatigue was 77.2% (housewife) and 84.1% (worker), numbness and tingling of the hands was 30.9% (housewife) and 31.9% (worker), backache was 63.8% (housewife) and 69.0% (worker), leg edema was 30.2% (housewife) and 39.8% (worker) and varicose veins was 20.4% (worker) and 24.2% (housewife). Prevalence of all symptoms differed in the 3 groups except numbness and tingling of the hands (p=0.626). The incidence of physical changes was as followed: 30.5% of the numbness and tingling of the hands occured during the second trimester while 62.5% occured during the third trimester, for backache 36.8% occured during the second trimester and 57.4% occured in the third trimester, for leg edema 17.8% occure during the second trimester and 81.1% happened during the third trimester. The incidence of varicose vein during the second trimester was 40.7% and at the third trimester 39.00/0. 22.12% of pregnant women reported reduce production as compared with non-pregnant women 14.9%. The prevalence of stress was significantly higher in the pregnant women (74.4%) compared with the non pregnant women (61.3%).. The study showed that abortion was more frequent in the working women (mean 0.25 ± 0.51 for pregnant worker and 0.42 ± 0.88 for non pregnant worker) than in the housewife (0.17 ± 0.45). In summary pregnancy increases the occurrence of physical signs of fatigue, numbness and tingling of the hands, backache, leg edema and varicose veins. It also increases the prevalence of stress and reduces productivity. To overcome these problems the following suggestions are made: that pregnant women- should be allowed to work flexi time, be given job adjustment when necessary, and the work place be made more conducive by having proper resting places so that pregnant women can lie down or rest their feet. It is also suggested that they should be given proper health guidelines on how to overcome the physical problems mentioned.